Peter Sloterdijk’s Technopolitics. How Technology Redesigns the Environment and the Polis - Della Torre, Cecilia (ETHICS IN PROGRESS, 2020)
This paper will analyse the role played by technology in Peter Sloterdijk’s theory, where he seeks to redefine and reconstruct ethics, society and democracy. Indeed, the philosopher’s project is to build a new kind of society, which risks being antidemocratic and elitist: technopolitics. This lemma refers to Sloterdijk’s reconfiguration of the social structure through the elimination of the human rights paradigm in a technological and anti-egalitarian manner. In order to do this, Sloterdijk redesigns the environment as a dangerous place whose rules cannot be followed, and which must be reshaped through technology. Hence, the philosopher reduces ethics to technology, and reinterprets society on the basis of new techno-ethical premises which support a hierarchical and selective new polis.